LEARNING MANAGEMENT STRATEGY IN IMPROVING BUSINESS AND PRODUCT MARKETING AT SMK NEGERI 2 SIMPANG KIRI KOTA SUBULUSSALAM - Erwinsah Putra; Fachruddin azmi; Inom Nasution (Research and Development Journal of Education, 2023)
One way to develop students' skills in line with the objectives of Vocational High Schools (SMK) is by formulating learning management strategies to create and market products through micro-businesses managed by the school. This research aims to determine: 1) Learning management strategies in improving products and marketing micro-businesses at SMK Negeri 2 Simpang Kiri, Subulussalam City. 2) Barriers in improving products and marketing micro-businesses at SMK Negeri 2 Simpang Kiri, Subulussalam City. 3) Efforts in improving products and marketing micro-businesses at SMK Negeri 2 Simpang Kiri, Subulussalam City. The research method uses a qualitative descriptive approach. Data collection is conducted through observation, in-depth interviews, and documentation. The data collection instrument is obtained through interviews with key informants. The data analysis procedure uses general data validity in qualitative research, namely data triangulation. The results of the research indicate that: 1) Learning management strategies to enhance products and micro-businesses involve hands-on practice methods in both product creation and marketing. It uses offline and online marketing strategies through social media. 2) The barriers to improving products and marketing micro-businesses include difficulties in obtaining materials, inadequate student skills, and an unfavorable geographical location. 3) Efforts to improve products and marketing micro-businesses involve continuous improvement in product quality and marketing. The school carries out marketing through both offline and online channels, meeting buyers in person and utilizing online platforms such as Facebook, WhatsApp, and Instagram.